2009
DOI: 10.1152/japplphysiol.00393.2009
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanical ventilation does not exacerbate lung function impairment or lung inflammation following influenza A infection

Abstract: The degree to which mechanical ventilation induces ventilator-associated lung injury is dependent on the initial acute lung injury (ALI). Viral-induced ALI is poorly studied, and this study aimed to determine whether ALI induced by a clinically relevant infection is exacerbated by protective mechanical ventilation. Adult female BALB/c mice were inoculated with 10(4.5) plaque-forming units of influenza A/Mem/1/71 in 50 microl of medium or medium alone. This study used a protective ventilation strategy, whereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
(47 reference statements)
3
13
0
Order By: Relevance
“…However, despite the application of these strategies, the morbidity and mortality associated with ARDS remain high, and the use of these low tidal volume ventilation strategies comes with the risk of atelectasis and the inflammatory response associated with derecruitment of the peripheral lung (31). In line with this, we have demonstrated that even so-called "protective" ventilation strategies using low tidal volume ventilation (to avoid overinflation) and periodic recruitment maneuvers (to maintain an open lung) can result in significant loss of lung volume and cytokine production in mice (9,40).…”
supporting
confidence: 61%
“…However, despite the application of these strategies, the morbidity and mortality associated with ARDS remain high, and the use of these low tidal volume ventilation strategies comes with the risk of atelectasis and the inflammatory response associated with derecruitment of the peripheral lung (31). In line with this, we have demonstrated that even so-called "protective" ventilation strategies using low tidal volume ventilation (to avoid overinflation) and periodic recruitment maneuvers (to maintain an open lung) can result in significant loss of lung volume and cytokine production in mice (9,40).…”
supporting
confidence: 61%
“…BEM et al [26] showed that infection with mechanical ventilation enhanced the response to pneumonia virus of mice (PVM) and might serve to exacerbate local inflammatory responses and lung injury. However, ZOSKY et al [27] showed that mechanical ventilation did not further exacerbate lung function impairment or lung inflammation following influenza A infection, using the same VT and mice species. No data exists on the consequences of VILI on RSV-induced pulmonary inflammation despite the fact that RSV infection is the most frequent cause of non-elective PICU admission for mechanical ventilatory support in infants during the winter season.…”
Section: Discussionmentioning
confidence: 98%
“…Bem et al (4) showed that infection with pneumonia virus of mice enhanced the response to mechanical ventilation (Vt, 10 mL/kg) and might exacerbate local inflammatory responses and lung injury. Interestingly, using the same Vt, Zosky et al (12) on the other hand showed that mechanical ventilation did not further exacerbate lung function impairment or lung inflammation following influenza A infection. This discrepancy in outcome might be attributable to either the differences in viruses or differences in experimental design.…”
Section: Discussionmentioning
confidence: 96%